. Solve π₯ 2 π 2π¦ π2π₯ β 2 ππ¦ ππ₯ β 4π¦ = 0Β
"\\displaystyle\nx^2\\frac{\\mathrm{d}^2y}{\\mathrm{d}x^2} - 2x\\frac{\\mathrm{d}y}{\\mathrm{d}x} - 4y = 0\\\\\n\n\\textsf{Let}\\,\\, y = f(\\ln{x})\\\\\n\n\\frac{\\mathrm{d}y}{\\mathrm{d}x} = \\frac{f'(\\ln{x})}{x}\\\\\n\n\\begin{aligned}\n\\frac{\\mathrm{d}^2y}{\\mathrm{d}x^2} &= -\\frac{f'(\\ln{x})}{x^2} + \\frac{f''(\\ln{x})}{x^2}\n&= \\frac{1}{x^2}\\left(f''(\\ln{x} - f'(\\ln{x})\\right)\n\\end{aligned} \\\\\n\n\nx^2\\left(\\frac{1}{x^2}\\left(f''(\\ln{x}) - f'(\\ln{x})\\right)\\right) - 2x\\cdot\\frac{f'(\\ln{x})}{x} - 4f(\\ln{x}) = 0\\\\\n\n\nf''(\\ln{x}) - f'(\\ln{x} - 2f'(\\ln{x}) - 4f(\\ln{x}) = 0\\\\\n\nf''(\\ln{x}) - 3f'(\\ln{x}) - 4f(\\ln{x}) = 0\\\\\n\n\n\\textsf{Let}\\,\\, t(l) = f(\\ln{x})\\\\\n\nt'' - 3t' - 4t = 0\\\\\n \n\\textsf{Auxiliary equation}; \\,\\,m^2 - 3m - 4 = 0\\\\\n\nm = -1, 4\\\\\n\nt = Ae^{-l} + Be^{4l} \\\\\n\nt = Ae^{-\\ln{x}} + Be^{4\\ln{x}} \\\\\n\nt(l) = f(\\ln{x}) = y = \\frac{A}{x} + Bx^4 \\\\\n\n\\therefore y = \\frac{A}{x} + Bx^4"
Comments
Leave a comment